Puitisasi Al-Qur’an: Telaah atas Terjemahan Al-Qur’an Karya H.B. Jassin - Arif , Muhammad Syaikhul (Al Furqan: Jurnal Ilmu Al Quran dan Tafsir, 2024)
During the transition period between the Old Order and the New Order, H.B. Jassin, known as Indonesia's "Pope of Literature," introduced a Quran translation using a poetic approach. His works, Al-Qur’anul Karim Bacaan Mulia and Al-Qur’an Berwajah Puisi, aimed to present the Quran with a distinctive aesthetic, namely poetry, intended to enrich the religious experience of its readers. This study aims to analyze the motivations, translation process, and the controversies surrounding this translation. By using a literature review and descriptive analysis approach, this study reveals that Jassin's translation process was full of personal struggles and public reception challenges. Moreover, this study highlights the uniqueness of Jassin's translation, which distinguishes it from the official translations of the Ministry of Religious Affairs. Despite facing significant criticism, this work made a substantial contribution by introducing a literary approach to translating religious texts, particularly the Quran, in Indonesia. This study also underscores the relevance of a literary approach in translating the Quran in a country rich in literary traditions and aesthetic values.